2014
DOI: 10.3892/ijo.2014.2759
|View full text |Cite
|
Sign up to set email alerts
|

miR-429 inhibits migration and invasion of breast cancer cells in vitro

Abstract: Accumulating evidence indicates that microRNAs (miRNAs) are involved in regulating cancer invasion and metastasis, and an increasing number of research demonstrates that miRNAs can promote or inhibit cell motility depending on genetic background of different cancers and the microenvironment. In the present study, we established an in vivo bone metastasis model of breast cancer by injecting MDA-MB-231 cells into the left ventricle of nude mice, and then screened the differentially expressed miRNAs between paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 39 publications
5
64
0
Order By: Relevance
“…In addition, overexpression of miR-429 inhibited PDAC cell growth via targeting TANK-binding kinase 1 (22). Ye et al (23) reported that miR-429 inhibited the migration and invasion of breast cancer cells via inhibition of zinc finger E-box binding homeobox 1 and Crk-like expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of miR-429 inhibited PDAC cell growth via targeting TANK-binding kinase 1 (22). Ye et al (23) reported that miR-429 inhibited the migration and invasion of breast cancer cells via inhibition of zinc finger E-box binding homeobox 1 and Crk-like expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed molecular mechanisms responsible for BC cell invasion remain unclear. Recently, miRNAs have emerged as an important mechanism responsible for BC cell invasion (29,30). In this study, we demonstrated that the expression levels of miR-214 were upregulated in BC tissues compared with adjacent benign tissues.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have demonstrated that miR-429 regulates oncogenic expression in human cells, including c-myc (28), onecut 2 (18), ZEB1 (30), v-crk avian sarcoma virus CT10 oncogene homolog-like (31) and B-cell lymphoma 2 (32). Therefore, upregulation of miR-429 or providing analogous pharmaceutical compounds exogenously may be effective cancer therapy for RCC, leading to the regulation of these oncogenic transcripts.…”
Section: Sp1 Is a Direct Target Of Mir-429 To Further Confirm Thatmentioning
confidence: 99%